Interaction of SARS-CoV-2 With RAS / ACE2 in the Female Reproductive System - Farideh Zafari Zangeneh (Tehran University of Medical Sciences, 2022)
Objective: The purpose of this review was to investigate current knowledge of COVID-19 by highlighting its effect on female reproductive tract. Materials and methods: In this study, all articles related to the effect of SARS, MERS, and CoV-19 viruses on the female reproductive system from 2003 to 2021 were reviewed. Results: The coronavirus enters the host cell by binding to the enzyme that is most abundant in the host lung. The corona or spike (S) protein of this virus is the main tool for binding to the receptor in the host cell membrane and facility the entrance of CoV into the target cells. This receptor is the Angiotensin-Converting Enzyme-2 (ACE2), but the high expression of this receptor can be a mystery to increase infection in host cells. The overexpression of ACE2 in different tissues has a close connection to the severity of this viral infection. Infection in the female reproductive system requires more attention because it may affect the generation and future progeny by damaged gametes. Conclusion: The existing evidence proposes that ACE2 is widely expressed in the reproductive tract includes: ovary, uterus, vagina, and placenta.